Head impact exposure in youth football - Are current interventions hitting the target? - Bahr Sandmo, S.; Andersen, T. E.; Koerte, I. K.; Bahr, R. (Scandinavian Journal of Medicine & Science in Sports, 2020)
Restrictions on heading in youth football have been implemented in some countries to limit head impact exposure. However, current interventions remain poorly guided by evidence. Our objective was to quantify heading exposure in youth football, assessing the effects of sex and age. Football matches played during an international youth football tournament with no heading restrictions were directly observed, including players from both sexes (11-19 years). The elite senior level was included for comparison, using video analysis. All heading events were registered, classified, and assigned to individual players. Heading rates were calculated for each sex and age group. We observed a total of 267 matches, corresponding to 4011 player hours (1927 player hours for females, 2083 player hours for males). Males headed more frequently than females (2.7 vs 1.8 headers/player hour; P < .001). Heading rates increased with age (ANOVA, P < .001), approaching the elite senior level for players 16 years and older. There was substantial variation within teams for all age and sex groups, with the widest range (1-18 headers) observed for girls aged 19. Girls younger than 12 years had the lowest exposure, with an average of <2 players per team heading the ball, each with 1-2 headers. In conclusion, age and sex influence head impact exposure in youth football, and warrants careful consideration when introducing injury prevention measures. Males are more frequently exposed than females, heading rates increase with age, and there is substantial variation between players. Heading is a rare event in the youngest age groups, especially among females.